University Admissions, Justice, and Virtue - Burns, David (Philosophical Inquiry in Education, 2022)
This analysis will argue that university educators have an ethical obligation to advocate for admission policies that are not exclusively competitive in nature – what will be referred to later as levelling and remedy approaches. This argument will be detailed in four stages. First, it will use an anecdote and an appeal to virtue to argue that educators in universities should feel an ethical obligation to level the playing field of competitive admissions. Second, it will draw on the work of a Chris Martin and Ben Kotzee to provide a philosophical framework for my argument. Third, it will discuss examples from Scotland, Ontario, and British Columbia to consider the ways in which the status quo fails to meet our ethical commitments as educators. Fourth, and finally, it will posit the virtue-ethical argument that university educators should live out their commitment to being virtuous and philosophy of education by supporting admission policies that are not exclusively competitive.